Naming Oneself Criminal: Gender Difference in Offenders' Identity Negotiation - Geiger, Brenda (International journal of offender therapy and comparative criminology, 2005)
This qualitative research examines gender differences in offenders'ability to negotiate a positive identity once the pejorative labels of criminal, prostitute, drug dealer, and incompetent parents have been imputed onto them. In-depth semi-structured focused interviews were conducted with a purposeful information-rich sample of eight male and eight female offenders. Content analysis reveals that males were much more adept than female offenders at juggling with conventional and street norms to justify and/or resist stigmatizing labels in order to construct a favorable identity. Appeal to such personal strengths as know-how, competence, loyalty, and a code of honor allowed male offenders to challenge the boundaries between conventional and delinquent worlds. Concomitantly such an appeal gave rise to a sense of efficacy perception and an optimistic explanatory style. In contrast, even though female offenders were able to justify the labels of drug dealer, prostitute, and thief by appeal to higher loyalties and reject that of insane, all their justifications collapsed when having to negotiate the identity of incompetent mother. Female offenders' negative internal attributions and deprivation of the normative center-motherhood resulted in apathy, anomie, and lack of confidence in their ability to do something worthwhile. Rehabilitation guidelines would build female offenders' personal strengths while redirecting those exhibited by male offenders into lawful enterprises